2007
DOI: 10.1021/op060249m
|View full text |Cite
|
Sign up to set email alerts
|

A Short and Efficient Synthesis of (R,R)-2-Methylcyclopropanecarboxylic Acid

Abstract: We report herein a short and efficient synthesis of (R,R)-2-methylcyclopropanecarboxylic acid via a Horner−Wadsworth−Emmons reaction involving commercially available (S)-propylene oxide and triethylphosphonoacetate (TEPA). The TEPA/base/propylene oxide stoichiometry was found critical to achieve high yields. We therefore studied the TEPA anion formation and stability using in situ IR spectroscopy. The reaction yield is strongly influenced by the counterion and solvent, whereas high diastereoselectivities are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…With the key intermediate 9 in hand, we next turned our attention to the synthesis of aldehyde 12 , which contains a trans ‐disubstituted‐cyclopropane moiety (Scheme ). Thus, commercially available ( S )‐2‐ethyloxirane 10 was subjected to optimized Wadsworth–Emmons cyclopropanation followed by an in situ saponification to furnish acid 11 in 82 % yield . This acid was then converted into homoallylic alcohol 11 a via a three‐step sequence involving a LiAlH 4 reduction to furnish the corresponding alcohol, a TEMPO promoted oxidation to give rise to an aldehyde and Brown allylation to set the third stereocenter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the key intermediate 9 in hand, we next turned our attention to the synthesis of aldehyde 12 , which contains a trans ‐disubstituted‐cyclopropane moiety (Scheme ). Thus, commercially available ( S )‐2‐ethyloxirane 10 was subjected to optimized Wadsworth–Emmons cyclopropanation followed by an in situ saponification to furnish acid 11 in 82 % yield . This acid was then converted into homoallylic alcohol 11 a via a three‐step sequence involving a LiAlH 4 reduction to furnish the corresponding alcohol, a TEMPO promoted oxidation to give rise to an aldehyde and Brown allylation to set the third stereocenter.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, commercially available( S)-2-ethyloxirane 10 was subjected to optimized Wadsworth-Emmons cyclopropanationf ollowed by an in situ saponification to furnisha cid 11 in 82 %y ield. [24][25][26][27][28] This acid was then converted into homoallylic alcohol 11 a via at hree-step sequence involving aL iAlH 4 reduction to furnish the corresponding alcohol, aT EMPO promoted oxidation to give rise to an aldehyde and Brown allylation to set the third stereocenter.P rotection of the homoallylic alcohol of 11 a as its benzyl ether,f ollowed by oxidative cleavage of the terminal olefin with OsO 4 and NaIO 4 to produce the required aldehyde 12 in 26 %overall yield from 11.…”
Section: Synthesis Of Aldehyde 12mentioning
confidence: 99%
“…The most common prototype, orginally reported by Wadsworth and Emmons, 9 entails the reaction of stabilized phosphonate anions with epoxides to form cyclopropanes (Figure 2A), a reaction process that typically requires both high temperature and prolonged reaction time. Independent studies by Singh, 11 Merschaert, 12 and Ghirardelli 5 suggested that the reaction proceeds through a mechanism similar to what we now term Type I ARC, involving a stepwise “Brook-like” rearrangement involving initial explusion of an ethoxide anion. Readdition of the ethoxide and completion of the C→O phosphorus migration furnishes a stabilized anion that undergoes intramolecular displacement of the diethoxyphosphate to generate the trans cyclopropane.…”
mentioning
confidence: 85%
“…While acid S39 is commercially available, it was prepared in house via an adaptation of a known literature procedure. 17 To an oven-dried 20 mL microwave vial containing a stir bar under argon were added triethyl phosphonoacetate (9.0 mmol, 1.8 mL, 1.0 equiv.) and anhydrous dioxane (9 mL, 1.0 M).…”
Section: (1r2r)-2-methylcyclopropane-1-carboxylic Acid (S39)mentioning
confidence: 99%